Komunikasi politik PDIP dalam mempengaruhi perilaku pemilih kota Surabaya - Didik Sugeng Widiarto; Muhtar Wahyudi; Moh. Edy Marzuki; Citra Rani Angga Riswari (Jurnal Komunikasi Profesional, 2023)
General Elections, or community participation in regional head elections, is a democratic method for selecting future leaders who can effectively lead their regions. A voter's behavior, influenced by their family and community, determines whether they will vote for a particular candidate in the general election. The purpose of this study is to ascertain how people in Surabaya vote in general election activities in Surabaya City. The descriptive qualitative research method was chosen in accordance with the objectives of the study. With a confidence level of 95% and a margin of error of +/- 2.31 percent, this study employs a survey method. Data collection was carried out using face-to-face interview techniques with questionnaire guidelines. The results of the study show that the majority of voters are very open to and influenced by the political communication activities of the candidates so that the behavioral characteristics of voters to elect members of the candidates are based on the selection of media and political channels (mass media, online media, and outdoor media), props and campaign attributes, as well as the activeness of legislative candidates on social media.